Indonesia : Enabling Water Utilities to Serve the Urban Poor - World Bank (Washington, DC, 2014)
The scope of this paper is limited to how donors and governments can stimulate owners to realize the potential of water utilities in serving the urban poor. As survey data indicates that reliable water utility service is a key aspect of serving the poor, this paper focuses on how Indonesian water utilities (PDAMs) can increase access to the poor. It also touches on tariff reform because the reluctance of PDAMs to connect the poor at an artificially low tariff creates a hindrance to overall reform. However, this discussion does not offer a comprehensive analysis or solutions to PDAM or tariff reforms, topics that have already been covered by several excellent studies. This study draws heavily on recent Indonesian survey data, while offering insights and first-hand accounts from those who have successfully managed water utilities in serving Indonesia's poor. Several water utility Diruts (Direktur Utama or a utility's Managing Director) have been able to serve the people by turning around weak utilities and guiding them to profitability. Their solutions on PDAM management appear in the annexes and apply mainly to PDAM reform, which is needed for sustainable service to the poor. This paper is more concerned with what can be done in the short term to move toward a system based on more reformed utilities that are led by motivated owners serving the poor. In general, while rural settlements are built up and maintained around water sources such as shallow wells, the quick spread of urban pollution due to crowding quickly eliminates clean water sources in those areas. Therefore, it is generally cheaper to find water in settled rural areas than in cities. Furthermore, the significant difference in Indonesia between the sometimes artificially low price of piped water and the high price people are willing to pay for it often results in serious social inequalities, including economic rents, illegal connections, water strongmen, water smuggling from social tariff to commercial tariff areas, and water theft.